Nghiên cứu phản ứng Diels–Alder của isopren với CH2=CH-Y (Y= -H, -C2H3, -C6H5, -CN, -COOH, -CHO, -NO2, -CH3, -OCH3) bằng phương pháp hóa học tính toán - Thọ, Nguyễn Hữu; Phong, Võ Thành (Vietnam Journal of Chemistry, 2016)
Effects of substituents on reactivity, stereoselectivity of Diels-Alder reaction of isoprene and derivatives of ethylene were investigated. The optimal structure of reactors and transition state were determined at B3LYP/6-311++G** level. Results from calculated HOMO, LUMO energies of dienophile component at HF/3-21G showed that when hydrogen atom in ethylene molecule is substituted by: -C2H3 (vinyl), -C6H5 (phenyl), HOMO energy increases and LUMO energy decreases. If it is substituted by electrophilic groups: -CN, -COOH, -CHO, -NO2, both HOMO and LUMO energies decrease, but if it is replaced by the nucleophiles (-CH3, -OCH3), both HOMO and LUMO energies increase. When electrophiles: -CN, -COOH, -CHO, -NO2 significantly reduce LUMO energy, the result is lessening the HOMO(isoprene) and LUMO(dienophile) gap and so the reaction occurs faster. The Frontier Molecular Orbital Theory cannot bring out a reliable prediction of reactivity of Diels-Alder reaction of isoprene and derivatives of ethylene with substituents: -C2H3, -C6H5, -CH3, -OCH3. Keywords. Diels-Alder, DFT, FMO, cycloaddition reaction, isoprene